2011
DOI: 10.1007/s10826-011-9465-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-Related Predictors of Self-Regulation Among Low-Income Youth

Abstract: The association between self-regulation and various adaptive outcomes has become a topic of growing interest to researchers. Yet, there is not much research on predictors of self-regulation in children. Using a crosssectional design and an array of psychometrically sound scales and measures from multiple informants, this study examined whether maternal characteristics, namely maternal mental health, substance abuse, parenting practices, and child monitoring predicted self-regulation in children. Participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…These results are consistent with previous research showing parenting behaviors and family functioning are related to child self-regulation 10,11,12 and impulsivity. 13 These results support family systems theories on the role of parenting and family functioning in shaping child characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous research showing parenting behaviors and family functioning are related to child self-regulation 10,11,12 and impulsivity. 13 These results support family systems theories on the role of parenting and family functioning in shaping child characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…Others have focused on selective dimensions such as sensitive responding and involvement, 10,11,12 limit setting and discipline 14 or control 13 and have focused on younger aged children. Our measure simultaneously captures these domains along with additional domains that are targets of family-based therapeutic approaches shown to decrease impulsive displays of behavior 35 and we include children in their preadolescent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have examined the specific aspects of the family context related to the experience of poverty that may affect the development of SR. Studies explicitly examining mediators of the income-SR relationship identified parenting quality, 14 housing conditions (crowding, safety and noise), 14,15 and lack of daily routine 15 as important factors linking income to child SR capabilities. Parental factors well known to be correlated with family income, such as parental mental health 16,17 and parenting style, 16,17 are also frequently linked to child SR ability. The role of broader socioeconomic indicators such as maternal education 16,18,19 and minority status, 18,19 in child SR has also been evaluated.…”
mentioning
confidence: 99%
“…Parental factors well known to be correlated with family income, such as parental mental health 16,17 and parenting style, 16,17 are also frequently linked to child SR ability. The role of broader socioeconomic indicators such as maternal education 16,18,19 and minority status, 18,19 in child SR has also been evaluated. These factors, however, have not been found to consistently correlate with child SR – perhaps because their effects, if any, are likely to operate through other mediating pathways.…”
mentioning
confidence: 99%